The Roles of Professional Engineers at the Institutions of Higher Learning in Nation-Building - Zambri, Harun; Nor Kamaliana, Khamis; Mohamad Dali, Isa; Zamri, Mohamed; Hashimah, Hashim (Canadian Center of Science and Education, 2013)
This paper discusses the roles of professional engineers (PEs) who are attached to the Institutions of Higher Learning (IHLs) and how their contributions are as important as their counterparts in the industry. This paper highlights the roles for PEs at IHLs based on a survey conducted at selected IHLs in Malaysia. Academician-professional engineers have crucial responsibilities to develop graduates who later promote safer and cutting-edge engineering solutions. These new technologies will make Malaysia an environmentally healthier place and further prepare Malaysia towards a developed nation at the end of the decade. From the survey, we conclude that PEs at IHLs make use of their professional qualifications to enhance their knowledge therefore provide better work quality. We also found that lecturers with these qualifications have higher confidence in their own ability to success in their careers and to face and help the public